Analysis of Determinants of Exclusive Breastfeeding in Breastfeeding Mothers - Purwaningsih, Dewi; Sudarmi, Sudarmi (Poltekkes Kemenkes Tanjung Karang, 2024)
Exclusive breastfeeding for babies aged 0-6 months, which continues until the age of 2 years accompanied by adequate complementary feeding, has an essential meaning, especially regarding the fulfillment of nutritional needs and other substances to form the body's immunity to disease, because at that age the baby's condition is still precarious. This study uses an analytic survey research cross-sectional design. The aim was to analyze the relationship between determinants of exclusive breastfeeding. The population of all mothers with babies aged 6-12 months amounted to 127, using a purposive random sampling technique. Sample calculation, according to Slovin, obtained a sample of 84. Data collection using a questionnaire. Univariate analysis with percentages, bivariate analysis with chi-square test. There is a relationship between knowledge (p-value=0.026), Early initiation breastfeeding (EIBF) history (p-value=0.005), breastfeeding self-efficacy (p-value=0.042), breastfeeding motivation (p-value=0.016), cultural customs (p-value=0.012), and family support (p-value=0.036) with exclusive breastfeeding in mothers who have babies aged 6-12 months at the Tanjung Sari Health Center, South Lampung Regency in 2024. A relationship exists between breastfeeding self-efficacy knowledge, motivation, and exclusive breastfeeding. There is a relationship between breastfeeding self-efficacy knowledge, breastfeeding motivation, cultural customs, and family support with exclusive breastfeeding. Suggested improving IEC (Communication, Information, and Education), implementing lactation management programs, making behavioral changes, and providing support for exclusive breastfeeding.